Neutropenia and eosinophilia among Ethiopian immigrants to Israel: Familial or environmental?. (1st October 2016) - Tandeter, Howard; Glick, Karina; Moser, Asher
ABSTRACT: Background: Due to trends of population movements, Israeli family physicians are treating increasing numbers of African immigrants from Ethiopia. These immigrants were found to have complete blood counts (CBC) that are different from other ethnic groups, with a higher prevalence of eosinophilia and neutropenia. Objectives: To evaluate haematological findings in an attempt to define whether they behave as familial (genetic) or environmental. Methods: Retrospective chart review of 300 patients from a primary care clinic: 100 individuals of Ethiopian heritage born in Ethiopia (EE); 100 individuals of Ethiopian heritage born in Israel, whose parents were born in Ethiopia (EI), and a control group of 100 patients who were not of Ethiopian heritage (C). Results: Absolute eosinophilia (greater than 500/dl) was found in 13% of the EE study group significantly higher than the two other groups ( P < 0.05), with no difference between EI and C. neutropenia (defined as less than 1500/dl) was found in 32% of EE group, 20% of EI, and 1% of C ( P < 0.01). Conclusion: On the one hand, findings point to a marked environmental influence on the eosinophilic response (most probably due to intestinal parasites present in immigrants from Ethiopia). On the other hand, a familial-genetic nature is probably the reason for the higher prevalence of neutropenia in this population, although some environmental influence may play a role. The knowledge of these findings may be useful for physicians treating people migrating from Africa.